2018
DOI: 10.1101/446104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-Cell Transcriptomics Unveils Gene Regulatory Network Plasticity

Abstract: Single-cell RNA sequencing (scRNA-seq) plays a pivotal role in our understanding of cellular heterogeneity. Current analytical workflows are driven by categorizing principles that consider cells as individual entities and classify them into complex taxonomies. We have devised a conceptually different computational framework based on a holistic view, where single-cell datasets are used to infer global, large-scale regulatory networks. We developed correlation metrics that are specifically tailored to single-cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…We have shown that prenatal TAM administration has broad effects from NPC proliferation, and cell differentiation to neural circuit formation. To reveal underlying molecular mechanisms, we carried out gene regulatory network analysis using bigSCale2 toolkit to identify hub genes that TAM employed to manipulate corticogenesis (Iacono et al, 2019). We chose to analyze NPC1/2 and CH clusters because the tight association between VZ NPC proliferation and cortical neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that prenatal TAM administration has broad effects from NPC proliferation, and cell differentiation to neural circuit formation. To reveal underlying molecular mechanisms, we carried out gene regulatory network analysis using bigSCale2 toolkit to identify hub genes that TAM employed to manipulate corticogenesis (Iacono et al, 2019). We chose to analyze NPC1/2 and CH clusters because the tight association between VZ NPC proliferation and cortical neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3,035 cells (CTL, 1,908 cells; TAM, 1,127 cells) were analyzed to generate a gene expression correlation network using bigSCale2 algorithm (Iacono et al, 2019). We discovered four major network modules in CTL and three modules in TAM treated cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical inferences at both individual gene level (Iacono et al (2019) and Yu (2018)) and gene set level, e.g., pathways, can be misleading without considering technical zeros.…”
Section: Introductionmentioning
confidence: 99%
“…Inference of gene-gene dependence, e.g., the correlation-based method, has been widely used in pathway analysis of bulk RNA-seq data (Zhang and Horvath, 2005), and recently also used in scRNAseq data analysis (Iacono et al, 2019;Yu, 2018;Pont et al, 2019;Van Dijk et al, 2018;Eraslan et al, 2019). However, correlation between two genes with technical zeros in the scRNAseq will not reflect the true gene-gene dependence.…”
Section: Introductionmentioning
confidence: 99%